+0  
 
0
59
1
avatar

if x*y=x-(y*x)-y, find

(a) (-3)*(-5)   (b)  (-5)*(-3) (c)

From the above results, state if x*y=y*x.

 
Guest Aug 13, 2017
social bar
Sort: 

1+0 Answers

 #1
avatar+18 
+1

a) 

-3 × -5 = -3 - (-5 × -3) - -5

-3 × -5 = 15

-3 - (-5 × -3) - -5 = -3 - 15 - -5 = -13

15 ≠ -13 ∴ the equation is false

 

b) Just do the same prosses but swap the numbers

-5 × -3 = -5 - (-3 × -5) - -3

-5 × -3 = 15

-5 - (-3 × -5) - -3 = -5 - 15 - -3 = -17

15 ≠ -17 ∴ the equation is false

 

c) x*y=y*x is true, but I don't get how doing x*y=x-(y*x)-y is supposed to prove if x*y=y*x is true or false since they're different equations. 

 
LARAUJO  Aug 14, 2017

11 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details